2021
DOI: 10.1002/bbb.2202
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing palm oil mill effluent (POME) for the immobilization of Aspergillus oryzae whole‐cell lipase strains for biodiesel synthesis

Abstract: Palm oil mill effluent (POME) is a palm industrial waste by‐product that is readily available and possesses high quantities of the organic compounds that are necessary for microbial growth. This study investigated the potential of immobilized Aspergillus oryzae whole cells expressing Candida antartica lipase B (r‐CALB) when using a POME‐based medium as a low‐cost carbon source within biomass support particles. The dry cell weight, hydrolytic activity, and remaining protein were measured for a variety of POME (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…Whereas COD level is usually at the range of 40,000-50,000 mg/L, where in this research, the COD concentration was higher at 67,145 mg/L than other COD measured in other researches such as 37,000-48,000 g/L [9] and 55,230 mg/L [44]. In addition, many studies have tried to utilize POME as a nutrient for culture fermentation media such as Bacillus cereus MF661883 to produce lipid [51], Phaeodactylum tricornutum (microalgae) to produce sulfated extracellular polysaccharide (eSPS) [70], and Aspergillus oryzae whole cells expressing Candida antartica lipase B (r-CALB) to produce immobilized wholecell biocatalysts [53] (Table 1). POME contains many organic materials, such as O&G, carbohydrates, free fatty acids (FFAs), highly concentrated nitrogenous compounds, and minerals (e.g., K, N, Mg, Ca, P, Fe, B, Zn, Mn, and Cu) that can support the growth of heterotrophic microorganisms, a potential substrate for microbial biomass, and could be beneficial for the cultivation of various types of microorganisms according to several studies [40,44,51,71].…”
Section: Characterization Of Palm Oil Mill Effluent (Pome)mentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas COD level is usually at the range of 40,000-50,000 mg/L, where in this research, the COD concentration was higher at 67,145 mg/L than other COD measured in other researches such as 37,000-48,000 g/L [9] and 55,230 mg/L [44]. In addition, many studies have tried to utilize POME as a nutrient for culture fermentation media such as Bacillus cereus MF661883 to produce lipid [51], Phaeodactylum tricornutum (microalgae) to produce sulfated extracellular polysaccharide (eSPS) [70], and Aspergillus oryzae whole cells expressing Candida antartica lipase B (r-CALB) to produce immobilized wholecell biocatalysts [53] (Table 1). POME contains many organic materials, such as O&G, carbohydrates, free fatty acids (FFAs), highly concentrated nitrogenous compounds, and minerals (e.g., K, N, Mg, Ca, P, Fe, B, Zn, Mn, and Cu) that can support the growth of heterotrophic microorganisms, a potential substrate for microbial biomass, and could be beneficial for the cultivation of various types of microorganisms according to several studies [40,44,51,71].…”
Section: Characterization Of Palm Oil Mill Effluent (Pome)mentioning
confidence: 99%
“…Furthermore, the significant amount of nutrients presents in the wastewater, resulting in an algae bloom [72]. Based on the potency of its components, POME could be used with treatment and aeration, which could serve as a suitable substrate to nourish and develop yeast and bacterial cells for CBL production [53,73].…”
Section: Characterization Of Palm Oil Mill Effluent (Pome)mentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen bond acceptor is acts important role to adsorption the hydrogen contained which makes FFA increases [19]. For conversion to biodiesel, we need waste-cookingoil that has a FFA content lower under 2% of FFA to avoid saponification during conversion process to biodiesel [20].…”
Section: Effect Of Extraction Time For Free Fatty Acid Reductionmentioning
confidence: 99%
“…In bioconversion, the rich organic residue in POME is used as a substrate for specific microorganisms to grow and consume while concurrently producing biomass and the targeted products, for example, bioenergy and biochemicals. Most researcher's studies were reported using POME as a substrate for bioenergy (Cheng et al, 2019;Hamid et al, 2019;Krishnan et al, 2019;Mamimin et al, 2016;Mishra et al, 2019;Prasertsan et al, 2021;Rachmadona et al, 2021;Rosa et al, 2020;Zaied et al, 2020). Studies on ultrafiltered POME concentrates or retentates as growth media for Penicillium chrysogenum in the production of antibiotics have been conducted some time ago (Suwandi, 1991;Suwandi & Mohammad, 1984).…”
Section: Introductionmentioning
confidence: 99%